Sosialisasi Kesadaran Hukum Atas Kepemilikan Tanah Bagi Masyarakat Di Desa Tarowang Kecamatan Galesong Selatan Kabupaten Takalar - Firman; Nurharsya Khaer Hanafie; Muhtar (Education and Talent Development Center Indonesia, 2025)
Community service was carried out to address the problem of the Tarowang Village community's low legal understanding regarding ownership, control, and administration of land certificates, which often triggers disputes and obstacles in legalizing land rights. The objective of this activity is to increase legal awareness among residents through comprehensive outreach regarding the importance of land legality, the use of certificate digitization as an alternative solution, and an understanding of the administrative flow of certificate processing. The methods used included legal counseling, expert presentations, interactive discussions, and mapping of land cases experienced by the community. The results of the activities demonstrated a significant increase in the community's understanding and ability to identify the legal status of their land, understand the benefits of digital land certificates, and prepare administrative documents more accurately and effectively. Overall, this community service program has had a tangible impact in the form of increased legal literacy and increased readiness to manage land legality as a form of rights protection and legal certainty.